The primary market of parking places against the background of the primary housing market and planning policy on the example of Krakow - Butryn, Krzysztof; Preweda, Edward (International Conference “Environmental Engineering”, 2017)
A decision taken on the primary market of real estate in parallel with the decision to purchase a dwelling, it is often the purchase of a parking space. As part of this work there were presented forms of providing space for parking, mostly encountered in practice. In the following, there were carried out the characterization of the primary market of parking spaces on the example of Krakow. There was made an attempt to indicate the potential attributes of price-setting for the valuation of the unit value of the discussed objects. Studies have shown that the price of parking spaces are formed in a different way than the market for residential and largely depend on individual factors, dependent on the sales policy developers. There were also indicated the difficulties that meets a real estate appraiser, whose task is to measure the market value of the parking space. The analysis also included the resolutions of existing planning documents in shaping the requirements for the number of parking spaces for multi-family residential areas in Krakow. Overview of planning documents from the Krakow, points to trends in the rules of applicable local spatial management plans in relation to the required number of parking spaces for newly established housing investment. At the same time in most parts of the city there is no planning guide lines regarding the subject matter.
Keywords: parking space; property valuation; land use planning